The adoption and success of contemporary management accounting practices in the Malaysian co-operatives sector - Sharul Effendy Janudin (Tanjong Malim, 2018)
The adoption and success of contemporary management accounting practices in the Malaysian co-operatives sector by Sharul Effendy Janudin